(3GdWQjbI GdeMeOjIs - (3eMeO Hf HjQ Ydj Hf EScfOQ GdHQcdj GdQhej , eMjj GdOjf, J (B981 (3g` s ((3EHQGgje Hf CHhHcQ s)
(3ChdgG (B:s
(3gPg GdQSGdI KdGKI CHhGH GdChd KdGKI aUhd GdaUd GdChd fhYGf GdfhY GdChd GdEYJUGe HGdcJGH GdcQje s
(3BNQgG (B:s
(3HEYWGA OQGge eYOhOI def jJdh GdbQBf hGdMeO ddg QH GdYGdejf s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B61 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B123 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B252s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1111s
Keywords: (3GdJUha hGdBOGH GdTQYjIs